MANAJEMEN TATA USAHA DAN KINERJA STAF TATA USAHA DI SMK TI LABBAIKA SAMARINDA - Heriman, Heriman; Komariyah, Laili; Subagiyo, Lambang; Warman, Warman (STIT Ibnu Rusyd Tanah Grogot, 2025)
This study aims to describe the administrative management and the performance of administrative staff at SMK TI Labbaika Samarinda. The main focus of the research encompasses three aspects: the process of formulating the school's vision and mission, the development of professionalism among educators and educational staff, and the implementation of improvements based on evaluations. The study employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings indicate that the process of formulating the school's vision and mission is carried out in a participatory manner, involving the principal, teachers, the school committee, and educational staff. The vision and mission are widely disseminated through print and electronic media. The development of staff professionalism is conducted continuously through internal training such as In-House Training (IHT), particularly at the beginning of the academic year and during curriculum updates. The implementation of program improvements based on evaluations is conducted regularly through monthly meetings involving all educators and educational staff. These evaluations serve as the basis for decision-making and the continuous improvement of the school's work programs. The study concludes that school management at SMK TI Labbaika has been carried out systematically and adaptively, emphasizing the importance of collaboration, professionalism, and continuous evaluation as key pillars in improving the quality of education.